2016
DOI: 10.1007/s10439-016-1689-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemically Doped Bioactive Borate Glass on Neuron Regrowth and Regeneration

Abstract: Peripheral nerve injuries present challenges to regeneration. Currently, the gold standard for nerve repair is an autograft that results in another region of the body suffering nerve damage. Previously, bioactive borate glass (BBG) has been studied in clinical trials to treat patients with non-healing wounds, and we have reported that BBG is conducive for soft tissue repair. BBG provides structural support, degrades in a non-cytotoxic manner, and can be chemically doped. Here, we tested a wide range of chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…49 Additionally, the effects of copper and/or zinc doped borate BGs have been evaluated in in vitro studies using fibroblasts, osteoblasts and endothelial cells considering similar BG compositions to those used in the present study. 40,45,46,48,[50][51][52][53][54][55] Although these published results are promising, they also showed that borate BGs, especially when doped with copper, could induce cytotoxic effects, particularly at high doses. 48,50 BGs have been extensively evaluated both in vitro and in vivo in their ability to improve bone and soft tissue regeneration, and so far several FDA approved BG compositions are commercially available in different forms (e.g.…”
Section: Biomaterials Science Papermentioning
confidence: 98%
“…49 Additionally, the effects of copper and/or zinc doped borate BGs have been evaluated in in vitro studies using fibroblasts, osteoblasts and endothelial cells considering similar BG compositions to those used in the present study. 40,45,46,48,[50][51][52][53][54][55] Although these published results are promising, they also showed that borate BGs, especially when doped with copper, could induce cytotoxic effects, particularly at high doses. 48,50 BGs have been extensively evaluated both in vitro and in vivo in their ability to improve bone and soft tissue regeneration, and so far several FDA approved BG compositions are commercially available in different forms (e.g.…”
Section: Biomaterials Science Papermentioning
confidence: 98%
“… Peripheral nerve regeneration Improved outgrowth of neurons and ratio of survival of neurons. Decreased survival of support cells [ 94 ] P 2 O 5 –CaO–MgO–Na 2 O–Ga 2 O 3 , up to 6 %Ga 2 O 3 Evaluation of the structural influence of gallium addition by NMR, FTIR, micro-Raman. Mechanical properties by nano-indentation.…”
Section: Gallium In Bioactive Glassesmentioning
confidence: 99%
“…It protects it from ROS damage (Perez et al 2008). Therefore, doping of bioactive glass with cerium ion can be useful for cancer treatment, and so, cerium has been incorporated in the bioactive glasses in previous studies (Leonelli et al, 2003;Zhang et al, 2010;Du et al, 2011;Shruti et al, 2012;Goh et al, 2014;Deliormanlı, 2015;Gupta et al, 2016;Nicolini et al, 2016Nicolini et al, , 2017Placek et al, 2018;Farag et al, 2019;Abbasi et al, 2021).…”
Section: Advances Inmentioning
confidence: 99%